2021
DOI: 10.1002/macp.202100274
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Thermal Processing on the Dynamic/Isothermal Crystallization and Cytocompatibility of Polylactic Acid for Biomedical Applications

Abstract: Polylactic acid (PLA) is a semi-crystalline biopolymer with numerous applications in tissue engineering and regenerative medicine. PLA biodegradable devices are usually manufactured by extrusion or injection molding. The crystalline-amorphous structure that PLA acquires during processing is relevant for its applications as it determines the biodegradation rate as well as the mechanical properties of the final device. This work focuses on the effect of processing and the effect of crystallization conditions ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 33 publications
1
3
0
Order By: Relevance
“…In this work, a decrease in M v of 22% was reported after five reprocessing cycles of PLA. Other researchers [18,38,65,67] found similar results, showing that [η] and M v can be used to measure process-induced degradation of PLA.…”
Section: Rheological Propertiessupporting
confidence: 52%
See 2 more Smart Citations
“…In this work, a decrease in M v of 22% was reported after five reprocessing cycles of PLA. Other researchers [18,38,65,67] found similar results, showing that [η] and M v can be used to measure process-induced degradation of PLA.…”
Section: Rheological Propertiessupporting
confidence: 52%
“…Multiple researchers investigated how the selected melt processing technique affects degradation. In the works of Carrasco et al [43], Cifuentes et al [67], and Pantani et al [92], the degradation due to SSE and IM was compared. Cifuentes et al [67] concluded a decrease in molecular weight of 8% PLDA via IM, whereas a decrease of 6% was observed for PLLA after SSE.…”
Section: Influence Of Processing Techniquementioning
confidence: 99%
See 1 more Smart Citation
“…4 Unfortunately, the slow crystallization rate and poor heat resistance of PLLA limit its large-scale application. 5 PLLA is a semi-crystalline polymer, 6,7 and the low crystallinity of PLLA after actual processing led to poor heat resistance. Current research has focused on improving the crystalline properties of PLLA by both adding nucleating agents to it and by post-molding heat treatment.…”
Section: Introductionmentioning
confidence: 99%